THE ROLE OF BEHAVIORAL VERBS IN VOCABULARY AND LANGUAGE SYSTEM - Elchaev Zohidjon Akhmatovich (Web of Journals Publishing, 2023)
This article explores the pivotal role of behavioral verbs in shaping and enhancing vocabulary within language systems. Behavioral verbs, which convey actions and behaviors, play a crucial role in enabling effective communication and expression. The article delves into the cognitive and linguistic mechanisms involved in the acquisition and utilization of behavioral verbs, highlighting their significance in fostering clarity, precision, and nuance in language. Additionally, the article examines the impact of behavioral verbs on language development, emphasizing their role in constructing vivid and dynamic narratives. The discussion encompasses pedagogical implications, focusing on strategies to enhance the teaching and learning of behavioral verbs to optimize language proficiency. Through an interdisciplinary lens, this article contributes to the broader understanding of the interplay between language, cognition, and communication, with a specific emphasis on the influential role of behavioral verbs in vocabulary enrichment.
Keywords: Cognitive Linguistics; Vocabulary Acquisition; Pedagogical Strategies; Language and Culture; Cognitive Dimensions.